KEDAH TUA CIVILISATION AT SUNGAI BATU TO BE NOMINATED AS A UNESCO HERITAGE - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
SUNGAI PETANI, KEDAH, 22 May 2016 - The Kedah Tua International Conference (KTIC) 2016 and Kedah Tua Festival (FKT) were organised to reveal the archaeological splendour at Sungai Batu and also to prepare the ancient site for nomination as a UNESCO World Heritage Site.